Influence of Multinational Enterprises on Local Industry Upgrading in Georgia - Kurdadze, Shorena (ANDULI, Revista Andaluza de Ciencias Sociales, 2020)
The purpose of this research is to identify Foreign Direct Investments in Georgia and to study their influence on the country’s economy by considering sector and country characteristics. To assess the impact of foreign direct investment on local economies, the author interviewed companies operating in Georgia in 2009-2016. Then, because the measurement scales used in the survey were mainly binary and ordinary, the author used ProbiT Regression and Ordered ProbiT Regression models. Results obtained from surveys and from analyses using regression equations show that natural resource-seeking companies use local goods and services in their production processes; this is expressed in their linkages with local suppliers and distributors. Conclusions are that foreign direct investments in Georgia have no significant influence on the development of local organizations and innovations. Although the Georgian market is small and the population is quite poor, market-seeking foreign direct investment is predominant. Multinational Enterprises that are directly engaged in foreign investments in Georgia (except for natural resources-seeking foreign direct investments), are rarely integrated with local markets.